Análise de viabilidade econômica e financeira para abertura de uma loja de produtos naturais na cidade de Paraí/RS - Cerbaro, Gabriela Mezzomo (2023)
This study was developed with the aim of analyzing the economic and financial viability of opening a natural products store in the city of Paraí/RS. Given the great demand for these products in local commerce and in neighboring cities, there is the possibility of opening an exclusive store, with affordable prices and diversity. The methodology used was the assumption of plans, being a descriptive research and presented in a quantitative way, addressing the main costs and expenses, revenues and initial investments using a target scenario of 60% in values. After calculations and analysis of financial indicators for the project, the results were positive, due to the fact that the initial investment of R$70,000.00 returned after the second year with a surplus of R$44,162.32. The VPL was positive, amounting to R$161,196.15 and the TIR was 70.39%. Therefore, it is concluded that the store's investment is considerable viable